X linked progressive cone dystrophy with specific attention to carrier detection. - van Everdingen, J A (1992)
We investigated 111 members of a five generation family with X linked cone dystrophy. The patients showed the characteristic picture of cone dystrophy. Routine ophthalmological examination of the carrier women showed no abnormalities. However, with detailed colour vision testing we were able to detect 87% of all obligate carriers.